A comparative study of the concept of time in The Blind Owl and its film adaptation based on the viewpoints of Henri Bergson and Gilles Deleuze - Ghazaleh Heydari Abkenar; Asgar Salahi; Hassan Akbari Beyragh (مطالعات زبانی و بلاغی, 2024)
: One of the common elements between literature and cinema is the subject of time, for which two characteristic features are observed; quantitative time, which is objective and qualitative time, which has a mental existence. Henri Bergson based his philosophical views of the concept of time on subjective consciousness. Later, Gilles Deleuze extended Bergson's view of time to cinema. The current research, a descriptive-comparative study, aims to investigate the concept of qualitative time based on the opinions of Henri Bergson and Gilles Deleuze in Sadeq Hedayat’s novel, The Blind Owl (Būff Cūr)  and its film adaptation, directed by Raứl Ruiz. According to this research, despite the difference in the written and visual media of literature and cinema, the concept of quality time is discerned as a common element in both works. To this end, the author and filmmaker have used a variety of internal time techniques, including diurnal cycles, intuition, reminiscences, time interferences, and time crystal components. Ruiz's film is a free adaptation, and its main plot and subplot are different from the novel. However, regarding the concept of time and the characteristics of mental time, it is consistent with Hedayat's effect. Among the findings of the present research, in addition to revealing the differences and similarities between the novel and the film from the perspective of qualitative time, it is possible to point out the common elements that can be adapted in literature and cinema based on the concept of time.